Vulnerability to Sexually Transmitted Infections in women who sell sex on the route of prostitution and sex tourism in Central Brazil - Marcos André de Matos; Karlla Antonieta Amorim Caetano; Divânia Dias da Silva França; Raquel Silva Pinheiro; Luciene Carneiro de Moraes; Sheila Araujo Teles (Universidade de São Paulo, 2013)
OBJECTIVE: to investigate knowledge on sexually transmitted diseases (STDs), STD-related risk behaviors, and signs/symptoms of STDs among female sex workers (FSWs). METHODS: a cross-sectional study was conducted with a probabilistic sample comprising 395 women recruited using a respondent-driven sampling method between 2009 and 2010. The data were collected during face-to-face interviews. RESULTS: most of the participants were young adults, had a low educational level, and had poor knowledge on the transmission paths of the human immunodeficiency virus (HIV). Over one-third of the participants were not able to describe the signs/symptoms of STDs. The prevalence rates of vaginal discharge and wounds/ulcers were 49.0% and 8.6%, respectively, but 41.7% of the women had not sought treatment. CONCLUSION: the results indicate the need for public health policies focusing on the control and prevention of STDs in this population, especially for the FSWs who are active in an important prostitution and sex tourism route in central Brazil.